Effect of co-occurrence of overweight/obesity and psychosocial stress dimensions on risk factors for cardiovascular disease among construction workers - Ekpenyong, Christopher E.; Davies, Koofreh (International Journal Of Community Medicine And Public Health, 2016)
Background: Many studies indicate that overweight/obesity and negative psychosocial states are independently associated with increased odds for cardiovascular disease (CVD) risk factors. However, the effect of the co-occurrence of these factors on CVD risk markers has not been adequately investigated, which was the focus of this study. Methods: The effect of overweight/obesity and psychosocial stress on CVD risk markers was cross-sectionally assessed via questionnaires and on-site physical examination at the construction companies’ site clinics and retained hospital. Overweight/obesity was ascertained using anthropometric indices and according to World Health Organization classification. Psychosocial work status was evaluated using a job content questionnaire. The association between overweight/obesity and psychosocial stressors and CVD risk markers was evaluated using multiple regression models when they occurred alone, and adjusted for sociodemographic factors when they co-occurred. Results: High social demand conferred 1.85, 2.38, 1.72, and 1.05 odds for hypertension, smoking, alcohol intake, and diabetes mellitus, respectively, in normal weight participants and 2.50, 4.01, 2.64, and 2.81 in obese participants. Likewise, low decision latitude and low social support conferred greater odds for CVD risk markers in overweight/obese versus normal weight participants. Conclusions: Overweight/obesity and psychosocial stressors increased the odds for CVD risk markers when they occurred alone, but conferred greater odds for CVD risk markers when they co-occurred, after controlling for the effect of potential confounders. In addition to psychosocial stressors, interventions at work sites to improve workers’ cardiovascular health should include other traditional CVD risk factors, such as overweight/obesity, to achieve complete success.